Similarities between calculated scission-neutron properties and experimental data on prompt fission neutrons - N. Carjan; M. Rizea (Physics Letters B, 2015)
The main properties of the neutrons released during the neck rupture are calculated for U236 in the frame of a dynamical scission model: the angular distribution with respect to the fission axis (on spheres of radii R=30 and 40 fm and at time T=4×10−21 s), the distribution of the average neutron energies (for durations of the neck rupture ΔT=1 and 2×10−22 s) and the total neutron multiplicity (for two values of the minimum neck-radius rmin=1.6 and 1.9 fm). They are compared with measurements of prompt fission neutrons during U235(nth,f). The experimental trends are qualitatively reproduced, i.e., the focusing of the neutrons along the fission axis, the preference of emission from the light fragment, the range, slope and average value of the neutron energy-spectrum and the average total neutron multiplicity.